The Gender Diversity in Corporate Governance, Board of Directors and Business Management: Literature Review 2011-2020 - Reynoso Espinoza, Deivit Wilfredo (2021)
The purpose of the article is showing a literature review of the empirical studies on gender diversity in corporate governance, board of directors, and management of companies. The literature review was carried out with articles collected in specialized and reliable databases. The review focuses on the most relevant research published in a 10-year period (2011-2020). The research among its results shows that there is a predominantly positive impact in the face of the increase in gender diversity in governments, boards of directors and managers. The impact has been measured in operational and financial terms from various theoretical perspectives. Among the theoretical approaches, agency theory, gender theory, and upper echelon theory, among others. This article compiles the recent empirical evidence that shows how significant is the inclusion of more women in the management bodies, boards of directors and corporate governments of companies can be, with scientific evidence.